Optimizing Public Parking System at Traditional Market - Putri, Dewa Ayu Putu Adhiya Garini; Nadun, Paskalis Aprianto; Kumara, I Nyoman Indra; Indrashwara, Decky Cipta (Fakultas Teknik Universitas Tanjungpura, 2024)
Urban parking management strategies, including paid parking, have proven effective in shaping transportation preferences and user behavior. These policies can yield positive outcomes such as decreased parking search times, enhanced parking space turnover, and a fairer allocation of parking resources among users. This study examines the parking characteristics and their impact on the surrounding area of Intaran Traditional Market in Denpasar, Bali. The market, operating from 4:00 am to 9:00 am daily, significantly affects traffic flow in the West Sanur area. Analysis of parking data revealed distinct patterns between off-street and on-street parking. While off-street parking duration was longer on weekends, on-street parking saw higher turnover rates. A one-way street system during market hours is proposed to address traffic congestion and improve parking management. This strategy aims to mitigate congestion and air and noise pollution in this mixed-use area. This research is focused solely on the parking of two-wheeled vehicles. Future studies could explore the interconnection between parking in this area and the condition of roads in the village of Intaran. Moreover, the economic potential of various parking management solutions could be a promising avenue for future research.